Cybersecurity behavior among government employees: The role of protection motivation theory and responsibility in mitigating cyberattacks - Noor Suhani, Sulaiman; M. A., Fauzi; Suhaidah, Hussain; Wider, Walton (MDPI AG, 2022)
This study examines the factors influencing government employees’ cybersecurity behavior in Malaysia. The country is considered the most vulnerable in Southeast Asia. Applying the protection motivation theory, this study addresses the gap by investigating how government employees behave toward corresponding cyberrisks and threats. Using partial least-squares structural equation modeling (PLS-SEM), 446 respondents participated and were analyzed. The findings suggest that highly motivated employees with high severity, vulnerability, response efficacy, and self-efficacy exercise cybersecurity. Incorporating the users’ perceptions of vulnerability and severity facilitates behavioral change and increases the understanding of cybersecurity behavior’s role in addressing cybersecurity threats—particularly the impact of the threat response in predicting the cybersecurity behavior of government employees. The implications include providing robust information security protection to the government information systems.